Prostaglandin D2 synthase: Apoptotic factor in alzheimer plasma, inducer of reactive oxygen species, inflammatory cytokines and dialysis dementia - John K. Maesaka; Bali Sodam; Thomas Palaia; Louis Ragolia; Vecihi Batuman; Nobuyuki Miyawaki; Shubha Shastry; Steven Youmans; Marwan El-Sabban (Society of Diabetic Nephropathy Prevention, 2013)
Background: Apoptosis, reactive oxygen species (ROS) and inflammatory cytokines have all been implicated in the development of Alzheimer's disease (AD). Objectives: The present study identifies the apoptotic factor that was responsible for the fourfold increase in apoptotic rates that we previously noted when pig proximal tubule, LLC-PK1, cells were exposed to AD plasma as compared to plasma from normal controls and multi-infarct dementia. Patients and Methods: The apoptotic factor was isolated from AD urine and identified as lipocalin-type prostaglandin D2 synthase (L-PGDS). L-PGDS was found to be the major apoptotic factor in AD plasma as determined by inhibition of apoptosis approximating control levels by the cyclo-oxygenase (COX) 2 inhibitor, NS398, and the antibody to L-PGDS. Blood levels of L-PGDS, however, were not elevated in AD. We now demonstrate a receptor-mediated uptake of L-PGDS in PC12 neuronal cells that was time, dose and temperature-dependent and was saturable by competition with cold L-PGDS and albumin. Further proof of this endocytosis was provided by an electron microscopic study of gold labeled L-PGDS and immunofluorescence with Alexa-labeled L-PGDS. Results: The recombinant L-PGDS and wild type (WT) L-PGDS increased ROS but only the WTL-PGDS increased IL6 and TNFα, suggesting that differences in glycosylation of L-PGDS in AD was responsible for this discrepancy. Conclusions: These data collectively suggest that L-PGDS might play an important role in the development of dementia in patients on dialysis and of AD.